2013
DOI: 10.1088/0004-6256/145/3/59
|View full text |Cite
|
Sign up to set email alerts
|

HIGHLY VARIABLE EXTINCTION AND ACCRETION IN THE JET-DRIVING CLASS I-TYPE YOUNG STAR PTF 10nvg (V2492 Cyg, IRAS 20496+4354)

Abstract: We report extensive new photometry and spectroscopy of the highly variable young stellar object PTF 10nvg (also known as IRAS 20496+4354 and V2492 Cyg), including optical and near-infrared time-series data as well as mid-infrared and millimeter data. Following the previously reported 2010 rise to R PTF 13 m . 5 and subsequent fade, during 2011 and 2012 the source underwent additional episodes of brightening, followed by several magnitude dimming events including prolonged faint states at R PTF 20 m . The obser… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
79
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(89 citation statements)
references
References 109 publications
9
79
0
1
Order By: Relevance
“…If the near-infrared magnitude changes were caused by changing extinction, then the difference in A V between the peak of the outburst and our faintest observation in 2011 July would be about 20 mag. We note that Hillenbrand et al (2013) observed the source at an even fainter state, indicating that the full range of extinction changes can be even higher. Remarkably, the faintest colors from 2010−2012 are still significantly different from the quiescent colors measured in 2006.…”
Section: Color−color and Color−magnitude Diagramsmentioning
confidence: 77%
See 3 more Smart Citations
“…If the near-infrared magnitude changes were caused by changing extinction, then the difference in A V between the peak of the outburst and our faintest observation in 2011 July would be about 20 mag. We note that Hillenbrand et al (2013) observed the source at an even fainter state, indicating that the full range of extinction changes can be even higher. Remarkably, the faintest colors from 2010−2012 are still significantly different from the quiescent colors measured in 2006.…”
Section: Color−color and Color−magnitude Diagramsmentioning
confidence: 77%
“…On shorter timescales, between 2011 August and December, the source seems to show ≈20-day-long quasiperiodic cycles. Recently, Hillenbrand et al (2013) presented well-sampled JHKs light curves and claimed to have found a 221-day period.…”
Section: Light Curvesmentioning
confidence: 99%
See 2 more Smart Citations
“…Objects like this are Hα11, PV Cep, V1647 Ori, and V899 Mon (Kun et al 2011a,b;Mosoni et al 2013;Ninan et al 2015). V346 Nor also resembles the young eruptive star V2492 Cyg in several aspects: the pre-outburst position of V2492 Cyg in the near-IR color-color diagram is close to the point of the 2010 minimum of V346 Nor, it also underwent a large accretion change at the beginning of its outburst, and in the high state, the line-of-sight extinction varies continuously (Kóspál et al 2011(Kóspál et al , 2013Hillenbrand et al 2013). Therefore, the observed variability in both V346 Nor and V2492 Cyg is governed by a combination of changing accretion and extinction.…”
Section: Discussionmentioning
confidence: 99%